2007
DOI: 10.1007/s11120-007-9247-0
|View full text |Cite
|
Sign up to set email alerts
|

Self-aggregation behavior of synthetic zinc 3-hydroxymethyl-13/15-carbonyl-chlorins as models of main light-harvesting components in photosynthetic green bacteria

Abstract: Zinc complexes of 3-hydroxymethyl-13/15-carbonyl-chlorins having a six-membered lactone as the E-ring were prepared by modifying purpurin-18 as models of bacteriochlorophyll-d, one of the chlorophyllous pigments in the main light-harvesting antenna systems (chlorosomes) of green photosynthetic bacteria. The synthetic 13-carbonylated compound self-aggregated in 1%(v/v) tetrahydrofuran and hexane to give large oligomers possessing red-shifted and broadened electronic absorption bands and intense circular dichroi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
5
0

Year Published

2008
2008
2014
2014

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 22 publications
2
5
0
Order By: Relevance
“…These indicated that 15-CO- 3 self-aggregated to form slipped overlapping J -aggregates (confirmed by largely red-shifted and broadened Soret band) inside a micelle, but the transition dipole moments of the composite molecules (especially Qy transition) would be disordered in the supramolecular structure due to the nonlinear order of OH, Zn and CO. In a previous report, zinc chlorin 6 possessing 13-CO self-aggregated similarly to the chlorosomal BChls while 7 possessing 15-CO failed to form such chlorosomal J -aggregates. A major difference between the previous and present studies is the skeletal π-system of the composite molecule: π−π stacking among the fully conjugated and more planar porphyrin π-system as in 3 should be stronger than that in chlorin 7 .…”
Section: Resultsmentioning
confidence: 78%
See 3 more Smart Citations
“…These indicated that 15-CO- 3 self-aggregated to form slipped overlapping J -aggregates (confirmed by largely red-shifted and broadened Soret band) inside a micelle, but the transition dipole moments of the composite molecules (especially Qy transition) would be disordered in the supramolecular structure due to the nonlinear order of OH, Zn and CO. In a previous report, zinc chlorin 6 possessing 13-CO self-aggregated similarly to the chlorosomal BChls while 7 possessing 15-CO failed to form such chlorosomal J -aggregates. A major difference between the previous and present studies is the skeletal π-system of the composite molecule: π−π stacking among the fully conjugated and more planar porphyrin π-system as in 3 should be stronger than that in chlorin 7 .…”
Section: Resultsmentioning
confidence: 78%
“…A small shoulder peak at around 560 nm might be induced from the Qx transition. These indicated that 13-CO- 2 self-aggregated in the aqueous micellar solution to make chlorosomal J -aggregates, similar to the self-aggregation of natural and synthetic chlorosomal chlorophylls. , ,,,,,,, …”
Section: Resultsmentioning
confidence: 81%
See 2 more Smart Citations
“…The Soret (B) band similarly shifts from 427 to 460 nm (33 nm; 1680 cm À1 ). Such spectral shifts, particularly that in the Q y band, are characteristic for self-assembled natural 58 and semisynthetic 27,59 analogues of the chlorosomal bacteriochlorophylls in nonpolar solvents.…”
Section: Photophysical Propertiesmentioning
confidence: 99%